LIFETIME OF AUXILIARY MACHINES OF AC ELECTRIC TRAINS - Baliichuk, O. Yu. (Science and Transport Progress, 2015)
Purpose. In this paper it is necessary to analyze increase the efficiency of auxiliary machinesof AC electric trains, series ER 9M during operating under the real conditions. Methodology. An engineering method to determine the relative reduction of the lifetime of asynchronous motors, selected with a certain design factor of power reserve, under normal operating conditions and with decrease of the electric power supply quality in auxiliary circuits of rolling stock, which takes place in real operation in sections of Ukrzaliznytsia was proposed. Findings. As a result of a study, conducted by the author it was found that long-term operation of asynchronous motors, selected with a sufficient reserve of power kз = 1,6, when the supply voltage unbalance is 16 … 20% leads to a reduction of their lifetime on 9,5…33,2%, depending on the type of motors. It proves that the choice of auxiliary machines with a large margin of power is not a rational way to increase the efficiency of auxiliary machines of electric trains, series ER9M. Recommendations were suggested for the introductions of symmetry-balancing and protective devices based on modern microprocessor and microcontroller hardware components. They make impossible operation of auxiliary machines during a low level of electric energy quality in onboard electric circuits of AC electric train in general, and on the trains, series ER9M in particular. Originality. The issues of the analytical study of the energy supply quality effect on the lifetime of auxiliary machines of AC electric trains, series ER9M through the determination of the relative reduction of the lifetime of auxiliary machines, depending on the general overheating temperature were highlighted firstly. The effect of safety factor for motor capacity on the average overheating and on the heating process of electrical machines on the whole was taken into consideration. Practical value. Obtained results allow forming critical opinion about the existing protection of auxiliary machines of AC electric train and develop recommendations for the implementation of complex organizational and technical measures to improve operability of auxiliary machines of AC electric trains, series ER 9M.